The sum and difference identity cos(x + y) / sin(x - y) = 1 - cotxcoty / cotx - coty is verified
Solution:
Given expression is:
![(\cos (x+y))/(\sin (x-y))=(1-\cot x \cot y)/(\cot x-\cot y)](https://img.qammunity.org/2020/formulas/mathematics/college/hezdiehi0jtrcnz7jijfttf0x38naegpxa.png)
Let us first solve L.H.S
------ EQN 1
We have to use the sum and difference formulas
cos(A + B) = cosAcosB – sinAsinB
sin(A - B) = sinAcosB – cosAsinB
Applying this in eqn 1 we get,
![=(\cos x \cos y-\sin x \sin y)/(\sin x \cos y-\sin y \cos x)](https://img.qammunity.org/2020/formulas/mathematics/college/jpydeaiy5ln7n44thgjexr2m4vvqz181qt.png)
![\text { Taking sinx } * \text { siny as common }](https://img.qammunity.org/2020/formulas/mathematics/college/gib1zw837ghgdnqlhjrilcln9cln9knr9l.png)
![=(\sin x \sin y\left((\cos x \cos y)/(\sin x \sin y)-1\right))/(\sin x \sin y\left((\cos y)/(\sin y)-(\cos x)/(\sin x)\right))](https://img.qammunity.org/2020/formulas/mathematics/college/i04b8d41k1dbml4mf4mobf19xb6pe189ct.png)
![\begin{array}{l}{=((\cos x)/(\sin x) * (\cos y)/(\sin y)-1)/((\cos y)/(\sin y)-(\cos x)/(\sin x))} \\\\ {=(\cot x * \cot y-1)/(\cot y-\cot x)} \\\\ {=(\cot x \cot y-1)/(\cot y-\cot x)}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/college/3bxngsyvthllbaia047p141rb70utm3vhb.png)
Taking -1 as common from numerator and denominator we get,
![\begin{array}{l}{=(-(1-\cot x \cot y))/(-(\cot x-\cot y))} \\\\ {=((1-\cot x \cot y))/((\cot x-\cot y))}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/college/u9at320k0emrhavir5zp6svlo64iw5236n.png)
= R.H.S
Thus L.H.S = R.H.S
Thus the given expression has been verified using sum and difference identity